GOOD FAITH AND FAIR DEALING IN HIRE PURCHASE CONTRACT IN MALAYSIA - Abdullah, Nurhidayah (Jurnal Syariah, 2019)
This paper aims to highlight the importance of the element of good faith and fair dealing in a hire purchase contract. This is because the attributes of honesty, reasonableness and fairness should be the underlying principles in every distinct hire purchase contract to connote the notion of ’fair dealing" transaction whereby the contract s sanctity is performed thus satisfYing the demand of the parties in the contract.